Design strategies for storm-water management on a major road in urban area (case study: a section of JEND. Sudirman Road, Jakarta) / Melania Lidwina Pandiangan ... [et al.] - Lidwina Pandiangan, Melania; Asriana, Nova; Santri, Tyas; Chandra Aditya, Nova (Universiti Teknologi MARA, Perak, 2022)
Abstract. Jakarta as a metropolitan city, experiences rapid growth urbanization, is struggling remarkably with flooding disasters. Regarding this condition, it is inevitable whether caused by frequent flooding of rivers as consequences of gradual sea level rising or affected by flash-flooding due to high rain rate and the expansion of impervious areas. Another condition on the existing drainage system in most areas in Jakarta carried the collected storm-water offsite and commonly caused flash flooding downstream. The study case area is a section of Jend. Sudirman Road-a major road in Jakarta that had frequent flooding challenges. This paper studies an alternative approach to drainage system or storm-water management through more integrated methods. The purpose is to develop the design strategies of storm-water management within an integrated system, not only by installing some small infiltration sets but also by improving urban resilience. This schematic design result will be a possible recommendation, especially the drainage system, to the local government. It leads subsequently to substitute and improve the existing drainage systems along this major road in the urban area.